Exposure to environmentally-relevant levels of ozone negatively influence pollen and fruit development. (November 2015) - Gillespie, Colin; Stabler, Daniel; Tallentire, Eva; Goumenaki, Eleni; Barnes, Jeremy
Abstract: A combination of in vitro and in vivo studies on tomato ( Lycopersicon esculentum Mill. cv. Triton) revealed that environmentally-relevant levels of ozone (O3 ) pollution adversely affected pollen germination, germ tube growth and pollen-stigma interactions – pollen originating from plants raised in charcoal-Purafil ® filtered air (CFA) exhibited reduced germ tube development on the stigma of plants exposed to environmentally-relevant levels of O3 . The O3 -induced decline in in vivo pollen viability was reflected in increased numbers of non-fertilized and fertilized non-viable ovules in immature fruit. Negative effects of O3 on fertilization occurred regardless of the timing of exposure, with reductions in ovule viability evident in O3  × CFA and CFA × O3 crossed plants. This suggests O3 -induced reductions in fertilization were associated with reduced pollen viability and/or ovule development. Fruit born on trusses independently exposed to 100 nmol mol −1 O3 (10 h d −1 ) from flowering exhibited a decline in seed number and this was reflected in a marked decline in the weight and size of individual fruit – a clear demonstration of the direct consequence of the effects of the pollutant on reproductive processes. Ozone exposure also resulted in shifts in the starch and ascorbic acid (Vitamin C) content of fruit that were consistent with accelerated ripening. The findings of this study draw attention to the need for greater consideration of, and possibly the adoption of weightings for the direct impacts of O3, and potentially other gaseous pollutants, on reproductive biology during 'risk assessment' exercises. Highlights: Environmentally-relevant levels of ozone exert negative effects on pollen viability that translate into direct impacts on fruit yield. Negative impacts of O3 pollution on reproductive processes were evident regardless of the stage of plant development. Exposure to environmentally-relevant levels of O3 resulted in shifts in fruit quality consistent with accelerated ripening. Abstract : Environmentally-relevant levels of ozone exert negative effects on pollen viability that translate into direct impacts on yield.